Composting of grease trap scum waste and green waste: Studying the effects of mix composition on physicochemical and biological process parameters - Santhoshi Chitthaluri; Polisetty Venkateswara Rao (International Journal of Recycling of Organic Waste in Agriculture)
Purpose A huge number of sewer blockages are caused due to scum depositions. The scum waste from the kitchen wastewater can be converted into a resource by composting it. This study investigates the degradation of Grease scum or Fats, oils, and grease (FOG) waste from grease trap with Vegetable waste (VW) and Grass clipping waste (GW) by passive aerobic bin composting for 55 days by evaluating variations in some of their physicochemical and biological process parameters.Method Five 80 L vertical composters were designed with a provision for leachate collection. Five mixes with varying FOG concentrations of 0%, 4%, 8%, 12%, and 16% with the rest of the mix containing VW and GW in 85:15 proportion in each bin was studied. Temperature, pH, EC, Moisture content (MC), Total volatile solids (TVS), Total Organic Carbon (TOC), Lipid content, and CO2 Evolution rate were monitored during the composting period.Results All the composting mixes maintained temperatures above 40˚C for 6-9 days and were found to be stable, with their final CO2 evolution rates in the range of 1.0 to 3.47 mg CO2-C/g VS/d at the end of composting. Mix 4 recorded maximum moisture, organic matter, and carbon content reduction with low CO2 evolution rate and so is the optimum mix containing FOG waste of 12%, VW of 74.8%, and GW of 13.2%. Conclusion Results in this study indicated that the grease scum waste can be significantly degraded when composted with suitable materials, but could require durations longer than this study period.